A novel flexible additive Weibull distribution with real-life applications. Issue 7 (3rd April 2021) - Khalil, Alamgir; Ijaz, Muhammad; Ali, Kashif; Mashwani, Wali Khan; Shafiq, Muhammad; Kumam, Poom; Kumam, Wiyada
Abstract: This paper introduces a novel model with six parameters called "flexible additive Weibull distribution (FAWD)." The suggested model is capable to model the life time data with a non-monotonic hazard rate. The statistical properties of the new distribution including Renyi entropy, quantile function, maximum likelihood estimation, order statistics, moment generating function, probability generating function, factorial and characteristic function are discussed in details. The flexibility of the proposed distribution is judged based on AIC, CAIC, BIC and HQIC, the smaller is the value of these statistics, and the better is the results. The usefulness of the proposed distribution is illustrated by using two real data sets. The proposed distribution has shown better performance and fits the used data better than some other well-known distributions.